1998
DOI: 10.1093/emboj/17.17.5129
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of mCtBP2, a co-repressor that associates with basic Kruppel-like factor and other mammalian transcriptional regulators

Abstract: Basic Krü ppel-like factor (BKLF) is a zinc finger protein that recognizes CACCC elements in DNA. It is expressed highly in erythroid tissues, the brain and other selected cell types. We have studied the activity of BKLF and found that it is capable of repressing transcription, and have mapped its repression domain to the N-terminus. We carried out a two-hybrid screen against BKLF and isolated a novel clone encoding murine C-terminal-binding protein 2 (mCtBP2). mCtBP2 is related to human CtBP, a cellular prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
359
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(374 citation statements)
references
References 54 publications
(113 reference statements)
15
359
0
Order By: Relevance
“…The GAL4 DBD-fused MEL1S expression constructs with various deletions and amino acid replacements were cloned into the pM expression vector (Clontech). The murine CtBP2 expression vector, pFLAG-CtBP2, contained a full-length murine CtBP2 (kindly provided by Dr Crossley; Turner and Crossley, 1998) cloned into the FLAG-epitope tag expression vector pFLAG-Mock. The human UBC9 expression vectors, pMyc-UBC9 and pMyc-UBC9DN, contain full-length human UBC9 and the dominant negative mutant (C93S), respectively, cloned into the Myc-epitope tag expression vector pMyc-Mock.…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…The GAL4 DBD-fused MEL1S expression constructs with various deletions and amino acid replacements were cloned into the pM expression vector (Clontech). The murine CtBP2 expression vector, pFLAG-CtBP2, contained a full-length murine CtBP2 (kindly provided by Dr Crossley; Turner and Crossley, 1998) cloned into the FLAG-epitope tag expression vector pFLAG-Mock. The human UBC9 expression vectors, pMyc-UBC9 and pMyc-UBC9DN, contain full-length human UBC9 and the dominant negative mutant (C93S), respectively, cloned into the Myc-epitope tag expression vector pMyc-Mock.…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…The molecular mechanisms by which KLF3 regulates transcription have been extensively analyzed. KLF3 recruits the transcriptional corepressor C-terminal binding protein (CtBP) to the promoters of target genes and is thus believed to act mainly as a repressor of transcription (5). In addition to the interaction with CtBP, full repression activity is dependent on sumoylation (6).…”
Section: Introductionmentioning
confidence: 99%
“…We limited the number of candidate proteins by examining only human proteins with established function in transcription regulation (Table 1). Among this list were many transcription factors known to act as negative regulators of transcription, most of which are already known to bind CtBP (25,27,28,30,(42)(43)(44)(45). Interestingly, we also identified several transcription corepressors, such as the proteins N-CoR, 5V-TG-3V-interacting factor, and methyl CpG -binding protein, proteins found in complexes with HDAC.…”
Section: Interaction Of Ctbp With Cbpmentioning
confidence: 88%
“…Recent work has shown that the CtBP protein, from either mammals or Drosophila, plays a role as a transcription corepressor through physical interactions with a variety of promoter-specific transcription factors (17,21,(23)(24)(25)(26)(27)(28)(29)(30). Indeed, expression of a Gal4 binding domain (Gal4BD)-CtBP fusion protein resulted in a substantial repression of the major late promoter (MLP) when assayed in C33A cells.…”
Section: Control Of Transcription By Ctbpmentioning
confidence: 99%
See 1 more Smart Citation